Ninth Workshop on Geothermal Reservoir Engineering: Proceedings - Ramey, H. J., Jr.; Kruger, P.; Miller, F.G.; Horne, R.N.; Brigham, W.E.; Gudmundsson, J.S. (Stanford University, 1983)
The attendance at the Workshop was similar to last year's with 123 registered participants of which 22 represented 8 foreign countries. A record number of technical papers (about 60) were submitted for presentation at the Workshop. The Program Committee, therefore, decided to have several parallel sessions to accommodate most of the papers. This format proved unpopular and will not be repeated. Many of the participants felt that the Workshop lost some of its unique qualities by having parallel sessions. The Workshop has always been held near the middle of December during examination week at Stanford. This timing was reviewed in an open discussion at the Workshop. The Program Committee subsequently decided to move the Workshop to January. The Tenth Workshop will be held on January 22-24, 1985. The theme of the Workshop this year was ''field developments worldwide''. The Program Committee addressed this theme by encouraging participants to submit field development papers, and by inviting several international authorities to give presentations at the Workshop. Field developments in at least twelve countries were reported: China, El Salvador, France, Greece, Iceland, Italy, Japan, Kenya, Mexico, New Zealand, the Philippines, and the United States. There were 58 technical presentations at the Workshop, of which 4 were not made available for publication. Several authors submitted papers not presented at the Workshop. However, these are included in the 60 papers of these Proceedings. The introductory address was given by Ron Toms of the U.S. Department of Energy, and the banquet speaker was A1 Cooper of Chevron Resources Company. An important contribution was made to the Workshop by the chairmen of the technical sessions. Other than Stanford Geothermal Program faculty members, they included: Don White (Field Developments), Bill D'Olier (Hydrothermal Systems), Herman Dykstra (Well Testing), Karsten Pruess (Well Testing), John Counsil (Reservoir Chemistry), Malcolm Mossman (Reservoir Chemistry), Greg Raasch (Production), ...